2019
DOI: 10.32479/ijefi.8551
|View full text |Cite
|
Sign up to set email alerts
|

The Factors Influencing Managerial Performance and Their Effect on Financial Accountability

Abstract: This study aims to examine and analyze the factors that influence managerial performance and their effect for financial accountability. By using an explanatory research method, this type of research is descriptive verification. Using primary data through surveys by providing research instruments to regional work unit tools at North Sulawesi. The collected data tested using the structural equation model method with partial least square approach. Simultaneous results of participatory budgeting, clarity of budget… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 10 publications
3
6
0
Order By: Relevance
“…Thus, this finding supports previous studies such as Bowrin (2004) and Saxton et al (2012), where there is an existence of such an indirect relationship between financial management practices and accountability. This empirical finding is also consistent with previous studies, which also found the mediating effect of internal control between financial management practices such as financial disclosure and financial performance on accountability (Kawatu and Kewo, 2019; Rafindadi and Olanrewaju, 2019).…”
Section: Resultssupporting
confidence: 92%
“…Thus, this finding supports previous studies such as Bowrin (2004) and Saxton et al (2012), where there is an existence of such an indirect relationship between financial management practices and accountability. This empirical finding is also consistent with previous studies, which also found the mediating effect of internal control between financial management practices such as financial disclosure and financial performance on accountability (Kawatu and Kewo, 2019; Rafindadi and Olanrewaju, 2019).…”
Section: Resultssupporting
confidence: 92%
“…According with the partial least square (PLS) analysis, this study shows that internal control has a positive effect on performance accountability. This study was corespondingly to previous research that internal control has a significant influence on performance accountability (Manullang & Abdullah, 2019;Fitrawati dkk, 2017;Kawatu & Kewo, 2019;Aprilianti et al, 2020;Tran et al, 2020). The First hypothesis (H1) in the study was accepted.…”
Section: Discussionsupporting
confidence: 55%
“…The internal control process provides guarantees for the management of resources economically, efficiently and effectively, ultimately impacting on improving performance accountability (Aprilianti et al, 2020). Internal control has a positive effect on performance accountability (Manullang & Abdullah, 2019;Fitrawati et al, 2017;Kawatu & Kewo, 2019;Aprilianti et al, 2020;Tran et al, 2020). Ningtyas et al, (2019) conducted research on local government, stating that internal control does not have a significant influence on performance accountability.…”
Section: Introductionmentioning
confidence: 99%
“…The results of previous studies explain that the internal control system affects the accountability of village fund allocation management (Azizah et al, 2015;Kawatu & Kewo, 2019;Antika et al, 2020). The internal control system must contain reconciliation procedures between budgeted financial transaction data and the realized budget to improve village fund accountability.…”
Section: Hypotheses Development Relationship Between Internal Control...mentioning
confidence: 98%